Effect of Audio-visual Aids on Students Understanding: A Comparative Analysis of JHS students in the Ho Municipality - ATIEKU, Joel Nunana; SEGBEFIA, Samuel Kwabla; GYAMPOH, Alexander Obiri (Integrated Journal for Research in Arts and Humanities, 2023)
The purpose of the study was to compare the level of understanding of students taught using audio-visual and those taught without using audio visual. The study employed quasi-experimental design. The study also revealed that the treatment group's students comprehended the material being taught to them. Students in the treatment group were able to give the right answers, give examples to back their responses, and only share their experiences if they were relevant to the answer, they gave during the evaluation of what they had been taught. The control group could not have been compared to this. The study also revealed that, in contrast to those in the control group, students in the treatment group were engaged and eager to take part in group projects and demonstrations throughout class. Students in the treatment group showed greater interest in class, but those in the control group were uninterested and passive. Finally, the test scores of the treatment group children were much better than those of the control group.